FORMULATION OF ISLAMIC CRIMINAL LAW POLICY AS A JURIDICAL INSTRUMENT FOR MAINTAINING THE BALANCE OF POWER AMONG STATE INSTITUTIONS - Suryadin, Suryadin; Arkiang, Bachder Syarif; Yumansyah, Diky; Mohammad, Burhanuddin; Syamsuddin, Syamsuddin; Musmuliyadin, Musmuliyadin; Putra, Anggar (Universitas Islam Negeri Mataram, 2025)
This study conceptually explores the possibility of integrating Islamic criminal law, particularly the doctrine of taʿzīr, into Indonesia’s constitutional framework of checks and balances. Rather than proposing an institutional mechanism, the paper normatively analyzes how Islamic ethical values such as ʿadl (justice), maslahah (public welfare), and hisbah (moral accountability) can enrich the moral foundation of state governance. The analysis is conducted through a qualitative normative approach based on secondary legal materials, including constitutional theory, Islamic jurisprudence, and contemporary scholarly discourse. The paper argues that taʿzīr, while traditionally applied to individual moral violations lacking explicit textual sanctions, may serve as a philosophical reference for enhancing ethical responsibility among state officials. However, this requires a clear epistemological distinction between taʿzīr as a moral-legal doctrine and checks and balances as a political-institutional system. The integration, therefore, should not be understood as a merger of institutional powers but as a normative dialogue between divine ethics and constitutional governance. The study concludes that Islamic criminal law contributes by offering an ethical corrective dimension to Indonesia’s democratic system, emphasizing moral accountability and justice without undermining legal pluralism or constitutional principles.